The Path Is the Goal: How Transformational Leaders Enhance Followers’ Job Attitudes and Proactive Behavior - Steinmann, Barbara; Klug, Hannah J. P.; Maier, Günter W. (Frontiers in Psychology, 2018)
While leading through goals is usually associated with a task-oriented leadership style, the present work links goal setting to transformational leadership. A longitudinal field study was conducted to investigate the influence of transformational leadership on followers’ job satisfaction, organizational commitment, and proactive behavior via goal attributes. Findings indicate that transformational leaders influence the extent to which followers evaluate organizational goals as important and perceive them as attainable. Multiple mediation analysis revealed that these goal attributes transmit the effect of transformational leadership on followers’ job attitudes and proactive behavior. However, goal importance and goal attainability seem to be of differential importance for the different outcomes.